Pemanfaatan Layanan Telemedicine pada Generasi Z di Kota Makassar - Marzuki, Dian Saputra (STIKES Yayasan RS.Dr.Soetomo, 2025)
Telemedicine is a technology-based health service that enables remote medical consultations effectively, particularly for communities in remote areas. Its usage in Indonesia continues to grow, especially among Generation Z. This study aims to identify the factors influencing the utilization of telemedicine services among Generation Z in Makassar City. The research design used was a cross-sectional study involving 320 respondents from SMAN 1, SMAN 5, and SMAN 21 Makassar, selected through accidental sampling. Data analysis was conducted using univariate and bivariate methods. The results showed significant associations between performance expectancy, effort expectancy, social influence, and facilitating conditions with the use of telemedicine (p < 0.001; p = 0.008; p < 0.001; p < 0.001). Additionally, performance expectancy and social influence were associated with telemedicine use based on gender (p = 0.023; p < 0.001), while effort expectancy showed no significant relationship by gender (p = 0.242). It is concluded that factors within the UTAUT model influence telemedicine utilization among Generation Z in Makassar, with gender moderating the relationship between performance expectancy and social influence.